The substantia nigra of the human brain. I. Nigrosomes and the nigral matrix, a compartmental organization based on calbindin D(28K) immunohistochemistry - Damier, P; Hirsch, E C; Agid, Y; Graybiel, A M (Brain (London, England : 1878), 1999)
Parkinson's disease is characterized by massive degeneration of dopamine-containing neurons in the midbrain. However, the vulnerability of these neurons is heterogeneous both across different midbrain dopamine-containing cell groups and within the substantia nigra, the brain structure most affected in this disease. To determine the exact pattern of cell loss and to map the cellular distribution of candidate pathogenic molecules, it is necessary to have landmarks independent of the degenerative process by which to subdivide the substantia nigra. We have developed a protocol for this purpose based on immunostaining for calbindin D(28K), a protein present in striatonigral afferent fibres. We used it to examine post-mortem brain samples from seven subjects who had had no history of neurological or psychiatric disease. We found intense immunostaining for calbindin D(28K) associated with the neuropil of the ventral midbrain. Within the calbindin-positive region, there were conspicuous calbindin-poor zones. Analysed in serial sections, many of the calbindin-poor zones seen in individual sections were continuous with one another, forming elements of larger, branched three-dimensional structures. Sixty per cent of all dopamine-containing neurons in the substantia nigra pars compacta were located within the calbindin-rich zone, which we named the nigral matrix, and 40% were packed together within the calbindin-poor zones, which we named nigrosomes. We identified five different nigrosomes. This organization was consistent from one control brain to another. We propose that subdivision of the human substantia nigra based on patterns of calbindin immunostaining provides a key tool for analysing the organization of the substantia nigra and offers a new approach to analysing molecular expression patterns in the substantia nigra and the specific patterns of nigral cell degeneration in Parkinson's disease.